Association between nighttime sleep duration trajectories and frailty in middle-aged and older adults: A work-in-progress model based on a CHARLS cohort - Yanling Zhou; Xiucheng Guo; Sunjuan Dong; Yimeng Wang; Mingming Zheng; Chi Wang; Li Wu; Weiting Liu (PLoS ONE, 2025)
Background Frailty is a major public health issue that impairs the quality of life and health outcomes of middle-aged and older adults. Changes in sleep patterns may play a critical role in the development of frailty. However, studies on the relationship between nighttime sleep duration trajectories and frailty risk remain limited. This study aimed to explore this association and provide preliminary evidence for frailty prevention and intervention. Methods Data were obtained from 8083 participants aged ≥ 45 years in the China Health and Retirement Longitudinal Study (CHARLS), assessed at four time points over seven years. Latent class trajectory modeling was applied to identify distinct nighttime sleep duration trajectories. Frailty was measured using a frailty index comprising 32 health deficits. Logistic regression was used to evaluate the associations between sleep trajectories and frailty. Results This study identified two nighttime sleep duration trajectories: normal stable trajectory group, encompassing 7137 (88.2%) individuals, and short with gradual increasing trajectory group, including 946 (11.7%) individuals. Compared with normal stable trajectory group, participants in short with gradual increasing trajectory group had a significantly higher incidence of frailty. Furthermore, after adjusting for covariates, this association remained statistically significant, although the effect size was modest. Conclusions Long-term exposure to short sleep may be associated with an elevated risk factor for frailty in middle-aged and older adults. Given the modest effect sizes observed, these findings should be interpreted as exploratory and part of a work-in-progress model. Continuous monitoring of sleep duration may still offer insights for early screening and prevention of frailty.